PENATALAKSANAAN DAN EXERCISE PADA DIABETES MELLITUS TIPE 2 DENGAN NEUROPATI PASIEN LAKI- LAKI LANSIA MELALUI PRINSIP PENDEKATAN KEDOKTERAN KELUARGA DI WILAYAH KERJA PUSKESMAS KEBON JAHE - Andra, Aditya; Mayasari, Diana (Medula, 2024)
Diabetes mellitus, a metabolic disorder characterized by elevated blood glucose levels due to insulin deficiency or insulin resistance, is a pressing global health issue, with more than 537 million people affected worldwide, according to WHO data from 2023, and an annual mortality rate of 1.5 million. In Indonesia, the prevalence of type 2 diabetes reached 19,572,564 cases in 2021, with Lampung reporting 38,923 cases. One key area of concern is the Kebon Jahe Community Health Center, which has recorded a high incidence of diabetes. A lack of awareness about diabetes contributes to a high rate of complications such as neuropathy, which can lead to damage to sensory, autonomic, and motor nerves in the peripheral nervous system if not well controlled. The management aimed to implement a holistic and comprehensive family physician approach tailored to the patient’s problems, utilizing evidence-based medicine that is patient-centered, family-oriented, and community-oriented. Primary data were obtained through auto-anamnesis, physical examination, and home visits. Secondary data were gathered from the patient’s medical records. Evaluations were conducted based on a holistic diagnosis from the initial process to the final study, analyzed qualitatively and quantitatively. Mr. H, a 66-year-old man, visited the Kebon Jahe Community Health Center with complaints of tingling and numbness in his hands for the past two months. The patient also reported frequent urination, excessive thirst, and increased hunger. He experienced weight loss of 3 kg over the past three months. A physical examination revealed a deficit in protopathic sensory function. The patient had a habit of consuming sugar from tea or coffee, adding 1-2 tablespoons in 5 servings daily. The patient’s knowledge about his condition was limited. Management was carried out according to related theories and journal guidelines. During the evaluation, the patient was able to adhere to both pharmacological and non-pharmacological therapy recommendations.